Self-Calibrated Double Luminescent Thermometers Through Upconverting Nanoparticles - Brites, Carlos D. S.; Martínez, Eduardo D.; Urbano, Ricardo R.; Rettori, Carlos; Carlos, Luís D. (Frontiers in Chemistry, 2019)
Luminescent nanothermometry uses the light emission from nanostructures for temperature measuring. Non-contact temperature readout opens new possibilities of tracking thermal flows at the sub-micrometer spatial scale, that are altering our understanding of heat-transfer phenomena occurring at living cells, micro electromagnetic machines or integrated electronic circuits, bringing also challenges of calibrating the luminescent nanoparticles for covering diverse temperature ranges. In this work, we report self-calibrated double luminescent thermometers, embedding in the same poly(methyl methacrylate) film Er3+- and Tm3+-doped upconverting nanoparticles. The Er3+-based primary thermometer uses the ratio between the integrated intensities of the 2H11/2-4I15/2 and 4S3/24I15/2 transitions (that follows the Boltzmann equation) to determine the temperature. It is used to calibrate the Tm3+/Er3+ secondary thermometer, which is based on the ratio between the integrated intensities of the 1G4-3H6 (Tm3+) and the 4S3/2-4I15/2 (Er3+) transitions, displaying a maximum relative sensitivity of 2.96% K−1 and a minimum temperature uncertainty of 0.07 K. As the Tm3+/Er3+ ratio is calibrated trough the primary thermometer it avoids recurrent calibration procedures whenever the system operates in new experimental conditions.